EVALUATION OF ONE DATA POLICY IN EAST JAVA - Nugroho, Angga Ariquint; Sukristyanto, Agus; Novaria, Rachmawati (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2024)
This East Java one data policy evaluation research aims to identify and analyze the evaluation of the one data policy in East Java Province. In this research the author used the qualitative research method Grounded theory. Grounded theory is a qualitative method for producing theory development using both inductive and deductive approaches, where in this research the author chose a deductive approach. Deductive approach by taking data sources from interviews with several informants implementing policies such as Bappeda, Kominfo, BPS, as well as representatives of data users. From this data, it is processed and concluded into findings and recommendations for the policy. The results obtained from this research are that East Java's one data policy has been running optimally and can be accessed by all data users. So that the need for data is increasingly met and openness to data is increasingly high. This really helps data users to improve performance and as material for making new policies for an agency.